2016
DOI: 10.4103/0255-0857.195375
|View full text |Cite
|
Sign up to set email alerts
|

Drug susceptibility of rapid and slow growing non-tuberculous mycobacteria isolated from symptomatics for pulmonary tuberculosis, Central India

Abstract: Drug sensitivity of NTM varies from species to species. While amikacin was the best for rapidly growing mycobacteria, clarithromycin was the most active drug against M. avium and other slow growers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
3
7
1
Order By: Relevance
“…We showed that 100% of the M. xenopi (n = 4) isolates were susceptible to streptomycin and amikacin; M. chelonae isolates (n = 2) were susceptible to ethambutol, streptomycin, and amikacin; M. fortuitum isolates (n = 11) were susceptible to amikacin, and Mycobacterium gordonae isolates (n = 2) were susceptible to streptomycin. Another study from India reported that the majority (95.2%) of the M. fortuitum isolates were susceptible to amikacin, which is similar to our findings (22). In our study, 100% of the M. fortuitum and M. chelonae isolates were susceptible to amikacin, which is in complete agreement with that reported in India and Taiwan (22,31).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We showed that 100% of the M. xenopi (n = 4) isolates were susceptible to streptomycin and amikacin; M. chelonae isolates (n = 2) were susceptible to ethambutol, streptomycin, and amikacin; M. fortuitum isolates (n = 11) were susceptible to amikacin, and Mycobacterium gordonae isolates (n = 2) were susceptible to streptomycin. Another study from India reported that the majority (95.2%) of the M. fortuitum isolates were susceptible to amikacin, which is similar to our findings (22). In our study, 100% of the M. fortuitum and M. chelonae isolates were susceptible to amikacin, which is in complete agreement with that reported in India and Taiwan (22,31).…”
Section: Discussionsupporting
confidence: 92%
“…Another study from India reported that the majority (95.2%) of the M. fortuitum isolates were susceptible to amikacin, which is similar to our findings (22). In our study, 100% of the M. fortuitum and M. chelonae isolates were susceptible to amikacin, which is in complete agreement with that reported in India and Taiwan (22,31). Similar to our findings, two other studies reported that 100% of the M. fortuitum isolates were susceptible to amikacin (32,33).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Over the past few years, much work has been reported [17][18][19] on hydrazone Schiff base ligands obtained by the reaction of aldehydes with 2-aminobenzoylhydrazide . Recently, it has been shown that the condensation of 2-ABH with aromatic and heterocyclic aldehydes yields ring-closed quinazolinone derivatives [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%